PENGARUH METODE DEMONSTRASI DAN MIND MAPPING TERHADAP PRESTASI BELAJAR MATA PELAJARAN SENI BUDAYA DITINJAU DARI KEAKTIFAN BELAJAR PADA SISWA KELAS VIII DI SMP SUB RAYON JAKENAN KABUPATEN PATI - AGUSTA PRAJABAWA, ANDRIK (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The purposes of this research are (1) to know the difference of Cultural Art Learning Achievement for the group of students who use demonstration method and the group of students who use mind mapping method, (2) to investigate the difference of Cultural Art learning achievement for the group of students who have high learning activeness and the group of students who have low activeness, and (3) to know the interaction of learning method and learning activeness in relation with the Cultural Art learning achievement. This investigation was done with a quantitative approach using an experimental method with 2x2 factorial designs. The population in this study were all eight grade students of SMP Sub Rayon Jakenan Pati Regency. In this study, the analysis technique used was the two-way analysis technique of variance (Two Way ANOVA). Based on the results of this research, it can be concluded that: (1) Studentsâ learning outcome of cultural art subject with demonstration method is better than students with mind mapping method. (2) Studentsâ learning outcome of cultural art subject who have high learning activeness is better than students who have low learning activeness. (3) Learning achievement of cultural art subject for the group of demonstration method with high learning activeness has the highest average score, while the group of mind mapping method with low learning activeness has the lowest average score.Keywords: demonstration method, mind mapping method, learning activeness, cultural art